Psychological and mechanical profiles of incarcerated male murderers in Malaysia - Kamaluddin, Mohammad Rahim (2015)
Murder is an unlawful act with the intention of killing a person. The increasingly violent murder incidents, incomplete characterisation of murder in Malaysia, inadequate Malaysian criminological studies on murder and murderers, and impacts and consequences of murder were pivotal in the desire to conduct this study on Malaysian male murderers. The present study is the pioneer national study that is conducted on murder by focusing on a sample of incarcerated Malaysian male murderers within Peninsular Malaysia. The main aim of the present study was to investigate their psychological and mechanical profiles. Nine specific objectives were formulated. The study commenced with a series of 11 year trend analyses to establish the trends and patterns of murder and murder victimology in Malaysia. Prior to the main study, a validation study was carried out to validate three psychometric instruments for the quantitative phase and the results were found acceptable and satisfactory. Following these, the main study employed explanatory mixed method research design using quantitative and qualitative approaches. In the quantitative phase, an observational cross-sectional design using a guided self administered questionnaire was applied for data collection. The sampling frame consisted of 71 Malaysian male murderers from 11 prisons who were selected using purposive sampling method with predetermined selection criteria. The questionnaire consisted of socio-demographic variables, mechanical variables of murder, and four Malay validated psychometric instruments: Zuckerman-Kuhlman Personality Questionnaire-40-Cross-Culture, Self-control scale, Aggression Questionnaire and “How I Think” Questionnaire. The present study also compares murderers and a control group (n = 300). Quantitative data were analysed using descriptive and inferential statistics. The descriptive findings successfully identified prevalent psychological and mechanical traits of male murderers. The regression analyses indicated that several personality traits have significant relationships and are predictive of other psychological variables. The correlation analyses highlighted several significant associations among the psychological variables. Findings revealed some significant mean and median differences of psychological variables score with the types of mechanical aspects committed by the murderers. The findings also indicated that there are several significant psychological traits differences between murderers and control group. In the qualitative phase, nine male murderers voluntarily participated in semi-structured interviews. Data were analysed using thematic analysis. Six main themes: violence and criminal history, substance abuse history, murder victimisation, murder victim concealment, psychological profiles, and preventive factors; were explored and several new themes emerged. The results were discussed in relation to murder, theories that underpin the present research, contexts of criminology and victimology.